2021
DOI: 10.3390/land10121365
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Archaeological Surface Ceramics Using Deep Learning Image-Based Methods and Very High-Resolution UAV Imageries

Abstract: Mapping surface ceramics through systematic pedestrian archaeological survey is considered a consistent method to recover the cultural biography of sites within a micro-region. Archaeologists nowadays conduct surface survey equipped with navigation devices counting, documenting, and collecting surface archaeological potsherds within a set of plotted grids. Recent advancements in unmanned aerial vehicles (UAVs) and image processing analysis can be utilised to support such surface archaeological investigations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…ArcGIS Pro contains built‐in libraries for deep learning, which have been used successfully for archaeological applications (e.g., Agapiou et al, 2021; Bickler & Jones, 2021; Davis et al, 2021; Davis & Lundin, 2021). To implement deep learning within the ArcGIS Pro environment, input data must be a multiband raster.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ArcGIS Pro contains built‐in libraries for deep learning, which have been used successfully for archaeological applications (e.g., Agapiou et al, 2021; Bickler & Jones, 2021; Davis et al, 2021; Davis & Lundin, 2021). To implement deep learning within the ArcGIS Pro environment, input data must be a multiband raster.…”
Section: Methodsmentioning
confidence: 99%
“…Machine learning and, specifically, deep learning hold the potential to increase the efficiency and success of lidar analysis across Oceania. Deep learning through convolutional neural networks (CNNs) has been applied with varying levels of success in other regions around the world (e.g., Agapiou et al, 2021; Bonhage et al, 2021; Davis et al, 2021; Guyot et al, 2021; Somrak et al, 2020; Soroush et al, 2020; Trier et al, 2019; Verschoof‐van der Vaart et al, 2020), and some approaches have successfully identified features even when training datasets are minimal (e.g., Davis et al, 2021). CNNs work by taking inputs from tensors (multidimensional matrices) to quantify multidirectional patterns, which allow neighbouring pixels to influence identifications (Caspari & Crespo, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This is essential in places where archaeological sites are difficult to access [127] . Two artificial intelligence approaches are introduced [128] over two areas of interest in the image processing field. They implemented a random forest classifier in their paper using the cloud platform of the Google Earth Engine data and a Single Shot Detector neural network is developed too.…”
Section: Archaeology Applicationsmentioning
confidence: 99%
“…It has experimented with geospatial data/images (satellite, aerial, lidar), texts, categorical tableau data, point clouds, and other datasets. For instance, one can consider some indicative examples such as the work that has been done on bone classification [1], remote sensing archaeology [2][3][4][5][6][7][8][9][10][11][12], geophysical prospection [13][14][15][16][17], detection of objects in paintings [18], classification of pottery [19], and the 3D reconstruction of heritage buildings [20]. The main reason behind this growing trend, which has been noticed in the last five years in all scientific domains, underlies the nuisance generated when dealing with multivariate analysis of high-volume datasets, which are challenging to process and interpret.…”
Section: Introductionmentioning
confidence: 99%